Variation in response to selenium folic acid and vitamin E in arsenic exposed aerobic flora in rats - Choudhry, ZK; Misbahuddin, M; Mojlish, UKFK (Bangladesh Journal of Medical Biochemistry, 2013)
Gut bacteria are considered to be body's first line of defense against ingested xenobiotics. Various nutritional and environmental factors play a role in bacterial growth and multiplication. Bacteria exposed to arsenic in high concentration for a long period showed growth inhibition. Influence of nutrition on bacterial growth and multiplication was observed by giving selenium (0.4 ?g/day), vitamin E (1 mg/day), folic acid (200 ?g/day) supplementation. Selenium and vitamin E were able to overcome the inhibitory effect of arsenic on gut flora. Selenium not only increased gut bacterial count, it also increased arsenic excretion in stool. Folic acid could not overcome the inhibitory effect of arsenic on gut flora but there was significant decrease in liver arsenic level suggestive of hepatic mehylation of arsenic. DOI: http://dx.doi.org/10.3329/bjmb.v4i2.13770 Bangladesh J Med Biochem 2011; 4(2): 13-16